Relação solo-vegetação em ecótono campo-floresta no bioma Pampa - Redin, Cristina Gouvêa (2017)
Studies that evaluate the relationship between flora and environmental variables are extremely valid, especially for conservation purposes in ecotone areas. In this way, the aim of this study was to evaluate the influence of environmental variables on grassland and forest phytophysiognomies in order to contribute for future elaboration of management and recovery plans and to respect the phytophysiognomies domain. The study was developed in two hortos located in the municipality of São Gabriel, being Horto Cerro do Batovi - HFCB - composed only by grassland vegetation and Horto Santa Olga - HFSO - composed of grassland and forest. The soil classification was performed in the summit, backslope and footslope of the relief throughout eight toposequences arranged in grassland vegetation, four in each horto. After that, from each horizon profile, samples with preserved structure were collected for soil physical properties analysis (soil density, Ks, soil porosity, CCPMP e AD) and samples with non-preserved structure for chemical analysis and soil granulometry. We also quantified the abundance of each herbaceous-shrub species in sample units of 1m², with four units in each toposequence evaluated in the summit, backslope and footslope. In order to verify the natural abundance of δ 13C ‰ in the vegetation samples of plant material were collected at the three relief positions at each toposequence. In HFSO, besides the grassland area, forest vegetation was evaluated in two fragments. In the first fragment (FFI), located in a fluvial terrace, 40 sample units (100 m²) and 40 subunits (4 m²) were allocated for inventory of the arboreal and regenerating strata respectively. Soil samples were collected at four points. In the second fragment (FFII), located in toposequence, 20 sample units and 20 subunits were allocated and soil samples were collected in four points. The forest and grassland vegetation were characterized by floristic, phytosociological and structural analyzes. The toposequences were characterized by physical, chemical and morphological properties of the soil. In order to infer about the possible flora-soil-relief relationships a multivariate statistical analyzes (PCA and CCA) were performed. Two time series were elaborated contemplating 15 years to verify vegetative changes in the study areas. The vegetation analysis showed differences among hortos due mainly to the proximity of fodder sources and grazing fallow time. HFSO presented higher frequency of species belonging, as well as grouping of forest individuals in the middle of the grassland and riparian forests. In HFCB, the riparian vegetation is composed naturally by grassland. These results corroborate the δ13C ‰ responses the material collected indicated predominance of C3 species in HFCB and a mixture of C3 and C4 taxa in HFSO. The forest vegetation occurrence is related to higher moisture and soil fertility, especially in lowland areas, but when assisted by rocky outcrops occurs in the summit and backslope of the relief. Species belonging to the families Cyperaceae, Isoetaceae, Apiaceae and Juncaceae were related to footslope conditions. During 15 years, there was an expansion of the forest fragments in HFSO, but in HFCB there were no changes in the phytophysiognomy demonstrating that the vegetation occurs naturally in the riparian environment.